2021
DOI: 10.21203/rs.3.rs-256745/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of Uptake of Intermittent Preventive Treatment for Malaria With Sulfadoxine Pyrimethamine in Pregnancy: A Cross-Sectional Study in the Sekondi-Takoradi Metropolis of Ghana

Abstract: BackgroundGhana malaria control programme recommends the uptake of five doses of SP during pregnancy following the review of the WHO recommendations in 2012. The uptake of higher doses of SP since the implementation of the new policy in 2016, has been low across the country. The current study determined factors that can be improved to increase uptake of IPTp-SP in malaria endemic regions. MethodsA descriptive cross-sectional study was carried out among women who had just delivered in selected health facilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The level of IPTp5 uptake (15.3%) in the current study is comparable to results from our earlier studies carried out in some parts of the country. Our rst hospital-based study conducted in Accra, the capital city and reported in 2017, documented 14% uptake of IPTp5, the second, this time in a rural setting (Navrongo) reported 16.0% in 2019 (5,25), and the third study reported a much lower level of uptake (< 7.0 %) in 2021 from Secondi-Takoradi (29).…”
Section: Univariate and Multivariable Analysis Of Factors Associated ...mentioning
confidence: 91%
“…The level of IPTp5 uptake (15.3%) in the current study is comparable to results from our earlier studies carried out in some parts of the country. Our rst hospital-based study conducted in Accra, the capital city and reported in 2017, documented 14% uptake of IPTp5, the second, this time in a rural setting (Navrongo) reported 16.0% in 2019 (5,25), and the third study reported a much lower level of uptake (< 7.0 %) in 2021 from Secondi-Takoradi (29).…”
Section: Univariate and Multivariable Analysis Of Factors Associated ...mentioning
confidence: 91%
“…Despite this progress, providing long-lasting insecticidal nets to rst-time mothers and extending SP to all pregnant women attending ANC services will signi cantly improve maternal and birth outcomes in Ghana (18). Previous studies conducted in Ghana have shown a correlation between SP uptake during pregnancy and several factors (19)(20)(21)(22)(23). For instance, De-Gaulle et al (2022) found that untrained health staff and stock-outs decreased SP uptake, while in a study by Kumah et al (2022), the number of ANC contacts, women's educational level, and time to the rst ANC contact were found to be predictive factors of SP uptake.…”
Section: Introductionmentioning
confidence: 94%